Modeling and Assessing of Omni-directional Robots with Three and Four Wheels - Hélder P. Oliveira (2009)
Robots with omni-directional locomotion are increasingly popular due to their enhanced mobility when compared with traditional robots. Their usage is more prominent in many robotic competitions where performance is critical, but can be applied in many others applications such as service robotics. Robots with omni-directional locomotion offer advantages in manoeuvrability and effectiveness. These features are gained at the expense of increased mechanical complexity and increased complexity in control. Traditional mechanical configuration for omni-directional robots are based on three and four wheels. With four motors and wheels, it is expected that the robot will have better effective floor traction (Oliveira et al., 2008), that is, less wheel slippage at the expense of more complex mechanics, more complex control and additional current consumption. Common robotic applications require precise dynamical models in order to allow a precise locomotion in dynamical environments. Such models are also essential to study limitations of mechanical configurations and to allow future improvements of controllers and mechanical configurations. The presented study is based on a single prototype that can have both configurations, that is, the same mechanical platform can be used with three wheels and then it can be easily disassembled and reassembled with a four wheeled configuration. A mathematical model for the motion of the robot was found using various inertial and friction parameters. The motion analysis includes both kinematical and dynamical analysis.